(untitled) (XXI Century. Spanish Literature and Culture, 2004)
The diversity of interests amongst readers and scholars of the subjects dealt with in Volverás a Región accentuates de lack of connection that said novel has with judicial discourse. For this, two intertwined perspectives are taken: the permeability of the narrative, which enriches the discoursive registers of the novel; and instances of the abandoned child that is its main character, such as affective laws and custom law – which presents a sort of incursion into the judicial field.